Accessibility and sustainable mobility transitions in Africa: Insights from Freetown. (December 2022) - Oviedo, Daniel; Cavoli, Clemence; Levy, Caren; Koroma, Braima; Macarthy, Joseph; Sabogal, Orlando; Arroyo, Fatima; Jones, Peter
Abstract: In the context of still-low-but-rising levels of motorization and economic growth, increasing social and spatial inequalities, and growing concerns about air pollution and climate change, the formulation and implementation of policies, practices and partnerships that can support an accelerated implementation of sustainable mobility policies is an urgent concern for rapidly developing cities. This paper seeks to contribute to reframing some of the knowledge and methodologies produced in and about cities of Sub-Saharan Africa, through a comprehensive assessment of mobility patterns and accessibility needs within a larger debate about mobility transitions and sustainable development. By deploying a mixed-methods approach that builds upon case-study focus groups and city-wide accessibility and mobility analysis in the city of Freetown, Sierra Leone's capital, the paper maps travel patterns and their links with structural factors such as urban form, poverty, informality and social identities at the macro, meso and micro levels. The paper also presents evidence from a variety of methods that illustrate the significance of accessibility-centred information and analysis for establishing policy priorities for improving urban mobility and accessibility in the local, African and global contexts.